2018
DOI: 10.2459/jcm.0000000000000656
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor-related late-onset dyspnea as cause of emergency department visit: a 3-year outpatient study

Abstract: Late-onset dyspnea rate is notably lower than early-onset one; nevertheless prescribing clinicians should be aware that about one in 20 outpatients with a stabilized ticagrelor treatment might develop a dyspnea leading to an emergency department visit, and they should consider ticagrelor replacement only in patients who cannot tolerate dyspnea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Three studies among the 11 included studies noted increased risk of dyspnea associated with ticagrelor use. This reiterates dyspnea as one of the acute side effects of ticagrelor which is reported and recognized in previous secondary analysis and cohort studies [27, 28]. However, the chronicity of dyspnea associated with ticagrelor use cannot be established in this analysis due to the limited long-term data.…”
Section: Discussionsupporting
confidence: 57%
“…Three studies among the 11 included studies noted increased risk of dyspnea associated with ticagrelor use. This reiterates dyspnea as one of the acute side effects of ticagrelor which is reported and recognized in previous secondary analysis and cohort studies [27, 28]. However, the chronicity of dyspnea associated with ticagrelor use cannot be established in this analysis due to the limited long-term data.…”
Section: Discussionsupporting
confidence: 57%
“…In recent years, some case reports and retrospective studies have shown that dyspnea associated with ticagrelor occurs not only in the early stages of drug treatment, but also may cause delayed dyspnea and even more dangerous Cheyne-Stokes (CSR) [6,7,8] . Because of this adverse event, the rate of discontinuation from 0.9-6.5% [9,10] , and one in 20 outpatients receiving a stabilized ticagrelor treatment might develop a dyspnea leading to an emergency room visit [11] .…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism of ticagrelor-induced dyspnea remains unclear [11,13] . There are several hypotheses (i)ticagrelor inhibits adenosine reuptake by red blood cell via inhibiting the sodium-independent equilibrative nucleoside transporter-1 (ENT-1).…”
Section: Introductionmentioning
confidence: 99%